Serologic survey of leishmaniasis in Ibn Sina patients, Sirte, Libya. - Shaban R. A. Bagar; Mohammed A. Daw; Fathi.s. Elkasah; Abdalla Mahdi etbiga (Sirte Journal of Medical Sciences, 2022)
The clinical and parasitological features of leishmaniasis were investigated, retrospectively, in 162 patients who attended the out-patient clinic of Ibn Sina hospital during January 2017 and June 2018. The aim was to evaluate the epidemiological characteristics of leishmaniasis. Sera from all the suspected patients were examined for slit and smear examination. Seventy one represent (43.82%) of 162 were positive. Of them, 52 (73%) were males and 19 (26.76%) females. The most affected age group was found to be between 21 and 30; the least affected was age group below 10 years.